Transfer factor, lung volumes, resistance and ventilation distribution in healthy adults. Issue 1 (19th November 2015) - Verbanck, Sylvia; Van Muylem, Alain; Schuermans, Daniel; Bautmans, Ivan; Thompson, Bruce; Vincken, Walter
Monitoring of chronic lung disease requires reference values of lung function indices, including putative markers of small airway function, spanning a wide age range. We measured spirometry, transfer factor of the lung for carbon monoxide ( T LCO ), static lung volume, resistance and ventilation distribution in a healthy population, studying at least 20 subjects per sex and per decade between the ages of 20 and 80 years. With respect to the Global Lung Function Initiative reference data, our subjects had average z-scores for forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC of −0.12, 0.04 and −0.32, respectively. Reference equations were obtained which could account for a potential dependence of index variability on age and height. This was done for (but not limited to) indices that are pertinent to asthma and chronic obstructive pulmonary disease studies: forced expired volume in 6 s, forced expiratory flow, T LCO, specific airway conductance, residual volume (RV)/total lung capacity (TLC), and ventilation heterogeneity in acinar and conductive lung zones. Deterioration in acinar ventilation heterogeneity and lung clearance index with age were more marked beyond 60 years, and conductive ventilation heterogeneity showed the greatest increase in variability with age. The most clinically relevant deviation from published reference values concerned RV/TLC values, which were considerably smaller than American Thoracic Society/European Respiratory Society-endorsed reference values. We present reference equations for median and variability of most lung function indices, in the age range 20–80 years http://ow.ly/SsZFW